PENGARUH KEMAMPUAN MANAJERIAL DAN STRATEGI KAPABILITAS DINAMIS TERHADAP KINERJA USAHA - Apsari, Gita Kartika; Rofiaty , Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
As age develops, business challenges escalate, and business environmental changes become more dynamic. These conditions require MSMEs to be more adaptive in applying strategies aimed at maintaining competitive advantages and boosting business performance. The objective of this quantitative research is to elucidates the causal relationship between its variables through hypothesis testing. Using purposive sampling, 55 owners of MSMEs that are still active in their sales and production during the research period were selected as the respondents. The data was harvested from questionnaires and interviews and analyzed using multiple linear regression in SPSS version 25. The results prove that managerial skill and dynamic capability partially have significant impacts on the business performance of the said MSMEs and that managerial skills and dynamic capabilities simultaneously pose some effects on the enterprises’ business performance. Therefore, it can be concluded that most of the MSME owners are capable of managing their business although it is not accomplished regularly and in a structured way. They also can apply the dynamic capability strategy well as their effort of overcoming the dynamic business environmental changes.